Does institutional innovation improve environmental performance? — a quasi-natural experiment based on China’s service trade innovative development pilot policy - Xu, Han; Wang, Siqi; Lei, Lei (Frontiers in Environmental Science, 2025)
This study employs Chinese urban panel data and a staggered difference-in-differences (DID) model to investigate the effects of China’s service trade innovative development pilot policy on environmental performance and its underlying mechanisms. The findings indicate that institutional innovation in the service trade sector substantially enhances regional environmental performance, and this conclusion remains valid after a series of validity tests and robustness tests. The mechanism test results show that institutional innovation can improve environmental performance mainly by promoting green innovation ability and industrial structure upgrading. Heterogeneity analysis found that regions with greater government support, a higher level of service industry development, and a higher degree of openness were more likely to rely on institutional innovation to improve their environmental performance. This research offers valuable policy insights for advancing institutional innovation in service trade and formulating pollution control strategies in China and other developing nations.